DNA Fingerprinting and its Role in Improving the Murder Crime (Indian Journal of Forensic Medicine & Toxicology, 2020)
The scientific development that was brought by modern civilization has left its clear imprints in the field ofbiology, which is directly reflected on the living cell and its relationship to genetics and formation. That Ithas recorded many scientific discoveries in the field that provided a wide opportunity to reveal some of thesecrets of the human cell. The science of cell study (cytology) is no longer limited to a purely descriptivestudy, but rather extended to the experimental study with the help of experimental embryology and analyticalstudies of the fertilization process, until the development of the scientific increases in the awareness of themajor fundamental issues that are related to cytological genetics which are the nature of the human gene andself-reproduction and how to perform his work in a report about these attributes, also this development hasextended to include the treatment of some genetic diseases, as this science has extended to the field of legalevidence (criminal and civil), this is because the traditional means which are used in evidence and improvingmay not achieve the justice or be insufficient to achieve them.